2014
DOI: 10.1021/es505075z
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Bioavailability and In Vitro Bioaccessibility of Perfluorooctanoic Acid (PFOA) in Food Matrices: Correlation Analysis and Method Development

Abstract: Food is a major source of human exposure to perfluorooctanoic acid (PFOA), however, PFOA bioavailability in food has not been studied. An in vivo mouse model and three in vitro methods (unified BARGE method, UBM; physiologically based extraction test, PBET; and in vitro digestion method, IVD) were used to determine the relative bioavailability and bioaccessibility of PFOA in the presence of 17 foods. PFOA was mixed with foods of different nutritional compositions and fed to mice over a 7-d period. PFOA relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 47 publications
2
38
1
Order By: Relevance
“…Apparently BA% values were not significantly different between native and spiked fish on the basis of either individual DDT components or total DDTs (Figure 2). This confirmed the validity of utilizing spiked samples 14,27,37 to mimic field samples in in vitro digestion experiments. At the same time, previous studies have documented that bioaccessibility was not affected by analyte concentrations at a fixed ratio of the digestive fluid volume to the mass of foodstuff.…”
Section: ■ Results and Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Apparently BA% values were not significantly different between native and spiked fish on the basis of either individual DDT components or total DDTs (Figure 2). This confirmed the validity of utilizing spiked samples 14,27,37 to mimic field samples in in vitro digestion experiments. At the same time, previous studies have documented that bioaccessibility was not affected by analyte concentrations at a fixed ratio of the digestive fluid volume to the mass of foodstuff.…”
Section: ■ Results and Discussionsupporting
confidence: 69%
“…Data Analysis. The bioaccessibility of DDTs and PBDEs in fish, defined as BA%, was calculated by the fraction of target compound mobilized from fish into the gastrointestinal phase with in vitro digestion 14,29…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For PCBs 52 and 118 in soil, the relative bioavailability measured in rats' blood was greater than 87% and could not be linked to their bioaccessibility measured by PBET, which produced underestimated results (40% to 80%) [68]. An in vivo/in vitro validation study was also undertaken for PFOA in food, and showed a good correlation (r=0.76, p<0.01) between PFOA bioaccessibility, assessed with the UBM method, and its bioavailability measured in rats' liver [70].…”
Section: Specific Human Populations Models Used For the Analysis Of mentioning
confidence: 99%
“…While an absorption efficiency of 91% was assumed for both PFOS and PFOA by Thompson et al (2010); other studies (Alves et al 2017;Li et al, 2015) have reported lower values of 11-99% for PFOA -with most solid foods below 70% -and 62 ± 5.6% for PFOS in fish. On this basis, we apply here an intermediate absorption efficiency value of 81%.…”
Section: The Model Is Expressed As Equation 2: (Equation 2)mentioning
confidence: 99%